2011
DOI: 10.1007/s11095-011-0564-9
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Silico Strategies to Identify OATP1B1 Inhibitors and Predict Clinical Drug–Drug Interactions

Abstract: PurposeTo establish in vitro and in silico models that predict clinical drug–drug interactions (DDIs) with the OATP1B1 (SLCO1B1) transporter.MethodsThe inhibitory effect of 146 drugs and drug-like compounds on OATP1B1-mediated transport was studied in HEK293 cells. A computational model was developed to predict OATP1B1 inhibition. Concentration-dependent effects were investigated for six compounds; clinical DDIs were predicted by calculating change in exposure (i.e. R-values) in eight different ways.ResultsSix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
136
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(146 citation statements)
references
References 48 publications
9
136
0
Order By: Relevance
“…The inserted sequence was verified by DNA sequencing analysis. Human embryonic kidney (HEK) Flp-In-293 cells (Invitrogen) were transfected with the constructed NTCP-pcDNA5/FRT expression vector and further selected using hygromycin B (Invitrogen), as previously described elsewhere (Karlgren et al, 2012a).…”
Section: Cloning and Establishment Of Stable Ntcp-hek293 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inserted sequence was verified by DNA sequencing analysis. Human embryonic kidney (HEK) Flp-In-293 cells (Invitrogen) were transfected with the constructed NTCP-pcDNA5/FRT expression vector and further selected using hygromycin B (Invitrogen), as previously described elsewhere (Karlgren et al, 2012a).…”
Section: Cloning and Establishment Of Stable Ntcp-hek293 Cellsmentioning
confidence: 99%
“…Mock-transfected HEK Flp-In-293 cells and cells stably expressing NTCP or either of the three OATP transporters [established and characterized by Karlgren et al (2012a,b)] were cultivated as described elsewhere (Karlgren et al, 2012a). Passages between 10 and 30 were used throughout the study.…”
Section: Cell Cultivationmentioning
confidence: 99%
“…14,16,17,33 Consistently, OATP inhibition explained the marked increase in the area under the plasma concentration-time curve of the OATP1B1 substrates bosentan and rosuvastatin, when co-administered with the combination of lopinavir and ritonavir in healthy volunteers. 34,35 In addition to the OATP1B inhibitory potential of HIV PI, several studies revealed that these drugs also show affinity for OATP1B isoforms as substrates.…”
Section: Discussionmentioning
confidence: 71%
“…12,13 Several studies have illustrated that HIV PI inhibit the in vitro cellular uptake of OATP1B probe substrates like estradiol-17β-D-glucuronide, CGamF and sodium fluorescein. [14][15][16][17] Moreover, it has been suggested that inhibition of these membrane transporters contributes to clinically important antiretroviral drug-drug interactions, for example with cerivastatin and atorvastatin. 18 While these examples certainly illustrate the clinical relevance of OATP modulation by HIV PI, the concept of meaningful OATPmediated transport of HIV PI remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The OATP subfamilies, OATP1B1, OATP1B3 and OATP2B1 were included in the dataset. A total of 142 compounds in this dataset was from an earlier investigation (Karlgren et al 2012b), which was then expanded to include compounds known to interact with OATPs or CYP enzymes (Karlgren et al, 2012a). The compounds were from the chemical space of oral drugs (Karlgren et al, 2012a).…”
Section: Oatp Inhibitorsmentioning
confidence: 99%